2021
DOI: 10.3389/fimmu.2021.620510
|View full text |Cite
|
Sign up to set email alerts
|

Function of Macrophages in Disease: Current Understanding on Molecular Mechanisms

Abstract: Tissue-resident macrophages (TRMs) are heterogeneous populations originating either from monocytes or embryonic progenitors, and distribute in lymphoid and non-lymphoid tissues. TRMs play diverse roles in many physiological processes, including metabolic function, clearance of cellular debris, and tissue remodeling and defense. Macrophages can be polarized to different functional phenotypes depending on their origin and tissue microenvironment. Specific macrophage subpopulations are associated with disease pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 109 publications
2
79
0
Order By: Relevance
“…iNOS is highly expressed upon activation of the transcription factor NF-κB in response to many stimuli and regulates the differentiation and function of immune cells via nitration of key molecules involved in transcriptional or signaling pathways [ 66 ]. When activated, M1 macrophages express pro-inflammatory cytokines, such as IL-1β, IL-6, and TNF-α [ 67 ]. IL-1β and TNF-α serve a critical role in leukocytes recruitment by promoting adhesion of leukocytes of the endothelium and their migration through blood vessels [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…iNOS is highly expressed upon activation of the transcription factor NF-κB in response to many stimuli and regulates the differentiation and function of immune cells via nitration of key molecules involved in transcriptional or signaling pathways [ 66 ]. When activated, M1 macrophages express pro-inflammatory cytokines, such as IL-1β, IL-6, and TNF-α [ 67 ]. IL-1β and TNF-α serve a critical role in leukocytes recruitment by promoting adhesion of leukocytes of the endothelium and their migration through blood vessels [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…M1 macrophages express pro-inflammatory cytokines such as IL1, IL6, IL12, IL23 and TNF-α. In contrast, M2 macrophages (or alternatively activated) are polarized by Th2 cytokines such as IL4 and IL13, producing anti-inflammatory cytokines such as IL10 and TGF-β [8, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Soldano et al [ 63 ] have demonstrated that M2 and cells expressing both M1 and M2 surface markers characterize patients with systemic sclerosis. A critical review of the functional phenotypes of macrophages according to their origins, tissue environments, disease progression, and their molecular mechanisms of development has been given by Zhang et al [ 64 ]. On the other hand, miR-125a-5p can target KLFI3, a transcription factor crucial for T lymphocyte activation and inflammation.…”
Section: Regulation Of Macrophage Polarization By Ncrnasmentioning
confidence: 99%